2021
DOI: 10.1002/mus.27368
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic yield of advanced genetic testing in patients with hereditary neuropathies: A retrospective single‐site study

Abstract: Introduction/Aims: Advanced genetic testing including next-generation sequencing (AGT/NGS) has facilitated DNA testing in the clinical setting and greatly expanded new gene discovery for the Charcot-Marie-Tooth neuropathies and other hereditary neuropathies (CMT/HN). Herein, we report AGT/NGS results, clinical findings, and diagnostic yield in a cohort of CMT/HN patients evaluated at our neuropathy care center.Methods: We reviewed the medical records of all patients with suspected CMT/HN who underwent AGT/NGS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
(136 reference statements)
1
1
0
Order By: Relevance
“…Four of five patients had molecular diagnosis who underwent WES analysis. The diagnostic yield was compatible with literature 20,21 . The diagnostic rate in pediatric age group (54%) was higher than adult age group (39%).…”
Section: Gnb4 Litaf Mfn2supporting
confidence: 84%
“…Four of five patients had molecular diagnosis who underwent WES analysis. The diagnostic yield was compatible with literature 20,21 . The diagnostic rate in pediatric age group (54%) was higher than adult age group (39%).…”
Section: Gnb4 Litaf Mfn2supporting
confidence: 84%
“…This approach has been transformed by the advent of NGS, where several disease-associated genes are tested in parallel. Nevertheless, the diagnostic rate of massive parallel sequencing tests described in the literature ranges from 4.6% to 93%, according to the analyzed cohort [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. In routine clinical practice, the NGS approach more realistically allows us to reach a genetic diagnosis in 30% of genetically undetermined patients when PMP22 duplication has been previously ruled out [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the number of CMT genes corresponding to the different subtypes continues to expand, the likelihood of identifying a causative genetic variant is increasing. In a retrospective, single-center study, gene panel testing of 108 patients with CMT identified 17 patients (15.7%) with pathogenic or likely pathogenic variants [55]. In a nationwide laboratory study in Japan, the combination of microarray, gene panel sequencing, and WES of 2598 cases identified pathogenic or likely pathogenic variants in 798 patients (30.7%) [56].…”
Section: Neuromuscular Disordersmentioning
confidence: 99%